Evaluating equity impacts of animal disease control: The case of foot and mouth disease in Zimbabwe - Randolph, Thomas F.; Morrison, J.A.; Poulton, C. (Oxford University Press, 2005)
As in other countries in southern Africa, foot and mouth disease (FMD) is endemic in certain parts of Zimbabwe inhabited by African buffalo, which harbor the virus. Despite this, Zimbabwe has invested for many years in maintaining freedom from FMD over much of its territory, permitting it to take advantage of favorable tariff arrangements for export of boneless beef and other livestock products to high-value markets in Europe. To maintain freedom from FMD, a zonation system implemented with fencing and movement controls has been used to protect a central export zone where much of the large-scale commercial farming is concentrated. Since 2001, Zimbabwe has suffered a series of FMD outbreaks, leading to a ban on the export of many livestock products, including beef. A high level of investment would now be required to re-establish FMD freedom and permit renewed export.